ADVANCING PLANT METABOLISM ANALYSIS: A REAL – TIME OPTICAL APPROACH, INSIGHTS FROM VRIESEA CARINATA WAWRA - Sara V. Ristić; Miloš S. Mošić; Marija M. Petković Benazzouz; Stefan Lekić; Katarina M. Miletić (STED Journal)
Optical detection of plant stress in real-time is crucial as it enables timely interventions to mitigate potential damage. This study presents a detailed evaluation of a system that detects changes in plant metabolism in real-time by distributing optical signals across the leaf. The methodology facilitates continuous monitoring of changes in the optical properties of plant leaves through measurements of optical transmission coefficients using a 665 nm LED light signal, thereby recording the circadian rhythm over time. Given that the photosynthetic processes within the leaves are closely linked to the plant’s overall health, this system can detect stress caused by various factors and identify metabolic changes by analysing the circadian rhythm patterns of the observed plants. For inducing metabolic changes, the plant Vriesea carinata Wawra, a verified representative of dual metabolism, was subjected to high light intensity stress. To validate the method, the collected results were compared with data obtained through chemical methods to establish a correlation between the traditional, destructive method and the non-destructive, optical method. The findings successfully identify circadian rhythms as parameters for recognizing changes in plant metabolism, demonstrating the significance of the proposed method in researching plant physiology through the optical identification of biological processes.